2021
DOI: 10.5194/hess-25-4861-2021
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes to forests during regeneration affect water flux partitioning, water ages and hydrological connectivity: Insights from tracer-aided ecohydrological modelling

Abstract: Abstract. Increasing rates of biodiversity loss are adding momentum to efforts seeking to restore or rewild degraded landscapes. Here, we investigated the effects of natural forest regeneration on water flux partitioning, water ages and hydrological connectivity, using the tracer-aided ecohydrological model EcH2O-iso. The model was calibrated using ∼ 3.5 years of diverse ecohydrological and isotope data available for a catchment in the Scottish Highlands, an area where impetus for native pinewood regeneration … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 108 publications
0
24
0
Order By: Relevance
“…At such locations, evaporative effects on grassland may become more influential than in a shaded forest with the deeper rooting systems and more distributed root water uptake across depth. Of course, the combination of many factors like topography, soil properties, and hydroclimatic conditions dictate soil water content VWC (see Neill et al, 2021; Zhu & Lin, 2011; Zucco et al, 2014). Nevertheless, in our study, the time dependent effects of dominant vegetation showed a clear influence on the patterns of ecohydrological partitioning of soil moisture variability, for example, forest soils tended to be drier compared to those under grassland.…”
Section: Discussionmentioning
confidence: 99%
“…At such locations, evaporative effects on grassland may become more influential than in a shaded forest with the deeper rooting systems and more distributed root water uptake across depth. Of course, the combination of many factors like topography, soil properties, and hydroclimatic conditions dictate soil water content VWC (see Neill et al, 2021; Zhu & Lin, 2011; Zucco et al, 2014). Nevertheless, in our study, the time dependent effects of dominant vegetation showed a clear influence on the patterns of ecohydrological partitioning of soil moisture variability, for example, forest soils tended to be drier compared to those under grassland.…”
Section: Discussionmentioning
confidence: 99%
“…However, beyond revealing absolute errors in the seasonal cycle, the stomatal conductance model based on sap flow also demonstrates that the Jarvis-Stewart model is not able to reproduce diurnal hydraulic feedbacks along the soil-plant-atmosphere continuum reflected in the dips in canopy conductance during the midday water stress period. Mechanistic understanding of these stress responses in plant-water flow is still limited and representing them using existing ecophysiological models is challenging, especially beyond the individual tree (e.g., Grossiord et al, 2020;Kannenberg et al, 2022;Novick et al, 2019). On the other hand, these dynamics are embedded in the sap flow data and were adequately reproduced by the RNN for the purpose of hydrological modeling.…”
Section: Integrating Sap Flow Data In a Catchment-scale Hydrological ...mentioning
confidence: 99%
“…One caveat R. Loritz et al: Leveraging sap flow data in a catchment-scale hybrid model to improve soil moisture in using these measurements is that they represent an effective flux integrating evaporation from the canopy interception store and the soil with plant transpiration. An accurate partitioning of this integral flux into its components is, however, of key importance for improving transpiration modeling under changing conditions (Stoy et al, 2019), including effects of land-use changes such as deforestation (e.g., Hrachowitz et al, 2021) and forest regeneration (e.g., Neill et al, 2021). This is a key reason why sap flow is used as independent measurement technique to characterize transpiration dynamics in forest (e.g., Granier and Loustau, 1994) and agricultural ecosystems (e.g., Dugas et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Such experimental "outdoor laboratories" are invaluable scientific resources given the complexity of increasing pressures on water supplies (e.g. Cosgrove and Loucks, 2015), land use change (Neill et al, 2021) and the uncertain effects and non-stationarity of projected climate change (Milly et al, 2015). Ecohydrology adopts an interdisciplinary approach to investigating interlinkages between the structure and function of ecological systems and the partitioning, flux and storage of fresh water (Guswa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%